In vitro N-Acetyl-l-Cysteine promotes proliferation and suppresses interleukin-8 expression in adipose-derived stem cells - Xiong, Lingyun; Hirche, Christoph; Lehnhardt, Marcus (Aesthetic plastic surgery, 2012)
Adipose-derived stem cells (ADSCs) hold great promise for repair and regeneration of burn wounds by producing growth factors, but proinflammatory cytokines such as interleukin-8 (IL-8) released by ADSCs would potentially deepen the wound and inhibit healing. The reported research aimed to identify the effects of N-acetyl-l-cysteine (NAC) on the proliferation, death, and IL-8 production of ADSCs. In the presence or absence of NAC, ADSC proliferation was examined using a CCK-8 Kit, and cell death was evaluated by flow cytometry analysis. Subsequently, IL-8 mRNA expression was detected by reverse transcriptase-polymerase chain reaction and protein production by enzyme-linked immunoassay. Findings showed that cell proliferation in the NAC-treated group was a significant 1.53-fold greater than in the control group, that the apoptosis rate of ADSCs decreased by 55.4 % compared with the control group, and that the necrosis rate decreased by 48.8 %. Additionally, the IL-8 mRNA expression decreased to 46.2 ± 8.7 % that of the control group, and the IL-8 protein production decreased to 9.98 ± 0.57 %. The authors believe that NAC might be helpful in burn wound repair and regeneration by stimulating the proliferation of ADSCs, inhibiting cell death, and suppressing IL-8 production.Level of Evidence IIThis journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.